High performance sol–gel spin-coated titanium dioxide dielectric based MOS structures. (December 2015) - Kumar, Arvind; Mondal, Sandip; Kumar, S. Girish; Koteswara Rao, K.S.R.
Abstract: High- κ TiO2 thin films have been fabricated using cost effective sol–gel and spin-coating technique on p-Si (100) wafer. Plasma activation process was used for better adhesion between TiO2 films and Si. The influence of annealing temperature on the structure-electrical properties of titania films were investigated in detail. Both XRD and Raman studies indicate that the anatase phase crystallizes at 400 °C, retaining its structural integrity up to 1000 °C. The thickness of the deposited films did not vary significantly with the annealing temperature, although the refractive index and the RMS roughness enhanced considerably, accompanied by a decrease in porosity. For electrical measurements, the films were integrated in metal-oxide-semiconductor (MOS) structure. The electrical measurements evoke a temperature dependent dielectric constant with low leakage current density. The Capacitance–voltage ( C – V ) characteristics of the films annealed at 400 °C exhibited a high value of dielectric constant (~34). Further, frequency dependent C – V measurements showed a huge dispersion in accumulation capacitance due to the presence of TiO2 /Si interface states and dielectric polarization, was found to follow power law dependence on frequency (with exponent ' s '=0.85). A low leakage current density of 3.6×10 −7  A/cm 2 at 1 V was observed for the films annealed at 600 °C. The results of structure-electrical properties suggest that the deposition of titania by wet chemical method is more attractive and cost-effective for production of high- κ materials compared to other advanced deposition techniques such as sputtering, MBE, MOCVD and ALD. The results also suggest that the high value of dielectric constant ' κ ' obtained at low processing temperature expands its scope as a potential dielectric layer in MOS device technology.